The Cytochrome P450-Catalyzed Oxidative Rearrangement in the Final Step of Pentalenolactone Biosynthesis: Substrate Structure Determines Mechanism - Duan, Lian (J Am Chem Soc, 2016)
The final step in the biosynthesis of the sesquiterpenoid antibiotic pentalenolactone (1) is the highly unusual cytochrome P450-catalyzed, oxidative rearrangement of pentalenolactone F (2), involving the transient generation and rearrangement of a neopentyl cation. In Streptomyces arenae this reaction is catalyzed by CYP161C2 (PntM), with highly conserved orthologues being present in at least 10 other Actinomycetes. Crystal structures of substrate-free PntM, as well as PntM with bound substrate 2, product 1, and substrate analogue 6,7-dihydropentalenolactone F (7) revealed interactions of bound ligand with three residues, F232, M77, and M81 that are unique to PntM and its orthologues and absent from essentially all other P450s. Site-directed mutagenesis, ligand-binding measurements, steady-state kinetics, and reaction product profiles established there is no special stabilization of reactive cationic intermediates by these side chains. Reduced substrate analogue 7 did not undergo either oxidative rearrangement or simple hydroxylation, suggesting that the C1 carbocation is not anchimerically stabilized by the 6,7-double bond of 2. The crystal structures also revealed plausible proton relay networks likely involved in the generation of the key characteristic P450 oxidizing species, Compound I, and in mediating stereospecific deprotonation of H-3(re) of the substrate. We conclude that the unusual carbocation intermediate results from outer shell electron transfer from the transiently generated C1 radical to the tightly paired heme-•Fe(3+)-OH radical species. The oxidative electron transfer is kinetically dominant as a result of the unusually strong steric barrier to oxygen rebound to the neopentyl center C-1(si) which is flanked on each neighboring carbon by syn-axial substituents.